Biblical Border Slippage and Feminist Postcolonial Criticism - McKinlay, Judith E. (The Oxford handbook of feminist approaches to the Hebrew Bible, 2020)
The essay takes as its cue the biblical figures of Eve and Wisdom, both of whom slip through the divine/human border. Eve brings knowledge of good and evil and Wisdom offers a concern for human ethical choices. For what characterizes feminist and postcolonial studies is the hope and ideal of a future of respect for all. A discussion of feminist postcolonial critical theory and current work in the field assesses that despite differing methodologies scholars share a concern for the ways in which women are represented and frequently “othered” in border-slipping texts. The study also considers a selection of biblical texts from a range of eras and political circumstances to illustrate these varying representations. The essay concludes with a reflection on the significance of the work and attempts to predict future directions.